2011
DOI: 10.1002/hbm.21455
|View full text |Cite
|
Sign up to set email alerts
|

Does sleep restore the topology of functional brain networks?

Abstract: Previous studies have shown that healthy anatomical as well as functional brain networks have small-world properties and become less optimal with brain disease. During sleep, the functional brain network becomes more small-world-like. Here we test the hypothesis that the functional brain network during wakefulness becomes less optimal after sleep deprivation (SD). Electroencephalography (EEG) was recorded five times a day after a night of SD and after a night of normal sleep in eight young healthy subjects, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 74 publications
6
39
1
Order By: Relevance
“…In any case, the disagreement between the two measures must be interpreted also as a caution signal towards the reliability of short connections modulation, and in this sense combining different measures is recommended. Previously, a combined phase-lag and SL study showed a large overlap between the two indices (Koenis et al, 2013), supporting the idea that SL is unlikely to be affected by volume conduction. Further studies are necessary to clarify the possibility of volume conduction effects on SL as well as to compare SL and phase lag indices.…”
Section: Discussionmentioning
confidence: 61%
“…In any case, the disagreement between the two measures must be interpreted also as a caution signal towards the reliability of short connections modulation, and in this sense combining different measures is recommended. Previously, a combined phase-lag and SL study showed a large overlap between the two indices (Koenis et al, 2013), supporting the idea that SL is unlikely to be affected by volume conduction. Further studies are necessary to clarify the possibility of volume conduction effects on SL as well as to compare SL and phase lag indices.…”
Section: Discussionmentioning
confidence: 61%
“…One explanation may be the increased variability in cortical excitability during sleep [28], which may originate from an altered functional network organization following sleep deprivation [29]. A mechanism, such as increased synchronization during sleep and after sleep deprivation, may also be a reflection of increased cortical excitability [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The state 'drowsiness' is often avoided in resting state research, because alertness or wakefulness is reduced during a drowsiness state and may vary and influence measurements greatly. However, recognizing drowsiness in resting state recordings can be difficult and requires a systematic approach (Koenis et al , 2013, van Diessen et al , 2014. Each state of vigilance has specific characteristics that contribute to differences in spectral power (Niedermeyer et al , 1987, Cantero et al , 1999 and functional connectivity (Kuhnert et al , 2010.…”
Section: State Of Vigilancementioning
confidence: 99%